The Collaborative Communication between the Task Force and Families in Building Resilience in Patients with Mental Illness - Nadya Wulandari; Sri Wahyuningsih (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2026)
The management of people with mental disorders (ODGJ) at the community level requires the active involvement of families and the Task Force (Satgas) as key actors in the support process. However, communication between the two parties often fails to function optimally and sustainably. This study aims to analyze and explore collaborative communication between the Task Force and families in building resilience and independence among ODGJ patients in Mandala Village, Sumenep Regency. This is a qualitative study using a descriptive approach.Data were collected through in-depth interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results indicate that collaborative communication evolves gradually from a reactive pattern toward a participatory one, yet remains dynamic and vulnerable to emotional pressures, differing perceptions, and limitations within the support system. The main findings of this study confirm that collaborative communication functions as a mechanism for social transformation within families, contributing to strengthening resilience and promoting patient independence. Therefore, a structured and sustainable communication system is needed in community-based care for people with mental health conditions.